(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
A staggering amount of solid municipal waste (MSW) is produced by one person daily in both developed and developing countries. However, by taking advantage of the situation, these solid waste could be converted into syngas; which are known to be potentially able to replace or mixed with natural gas for industrial and everyday energy applications. As well, existing treatment and processing of biomass and solid fuels such as coals has been widely used in industrial scale to generate electricity. This paper reviews the previous studies on plasma treatment for the processing of solid waste, which would be helpful in the production of syngas. Plasma technology is one of the efforts to practice sustainable cleaner technology for the industrial world. The types of plasma technology reviewed are thermal plasma, microwaves plasma, and radio frequency plasma. Other than processing and treatment of solid waste, plasma technology could also be applied in other area such as environmentally, decontamination of chemical and biological warfare agents and nanotechnology. As well, plasma technology could help in creating a greener world by lowering the greenhouse gas emissions from heavy industries. It is hoped that this review could put a light on the future direction of MSW management situation in Malaysia.